Effectiveness of Nursing Care Management Using Digital Education in Improving Dietary Adherence among Patients with Diabetes Mellitus - Supriyanti Supriyanti; Afnina Afnina; Siti Syafiqah Shada; Elfida Elfida; Eva Sulistiany (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Diabetes Mellitus (DM) is a chronic disease that requires long-term management, particularly with regard to dietary regulation. Dietary adherence remains one of the major challenges among patients with DM, as it is influenced by multiple factors, including knowledge, motivation, and continuous support from health care professionals. Advances in digital technology have created new opportunities for delivering health education in a more flexible and sustainable manner. This study aimed to analyze the effectiveness of nursing care management supported by digital education on dietary adherence among patients with Diabetes Mellitus in Langsa City, Aceh Province. This study employed a quasi-experimental design using a pretest–posttest approach with a control group. A total of 60 patients with type 2 Diabetes Mellitus were recruited and assigned to either an intervention group or a control group. The intervention consisted of digital education delivered through WhatsApp and visual educational materials over a 14-day period. Dietary adherence was assessed using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. The results demonstrated a statistically significant improvement in dietary adherence scores in the intervention group compared with the control group (p < 0.05). These findings indicate that digital education integrated into nursing care management is effective in improving dietary adherence among patients with Diabetes Mellitus. Therefore, digital education may serve as an alternative strategy in nursing practice to support the sustainable management of Diabetes Mellitus.